American Muslims and the Obama administration - Nimer, Mohamed 1960- (Emirates lecture series v 82, 2010)
President Barack Hussein Obama began his first term in office with aggressive pronouncements of a change in the course of America's relations with the Muslim world. One year into his presidency, Obama's policies toward US Muslims appear to continue on the path set by his predecessor. This is the prevailing perception among the immigrant-dominated Arab and Muslim community groups in the United States. This paper will explore the growth of the Muslim community in the United States, the place of activist organizations in the community, their responses to assimilation, and the prospects for community-government dynamics